Fit-For-All iPSC-Derived Cell Therapies and Their Evaluation in Humanized Mice With NK Cell Immunity - Flahou, Charlotte; Morishima, Tatsuya; Takizawa, Hitoshi; Sugimoto, Naoshi (Frontiers in Immunology, 2021)
Human induced pluripotent stem cells (iPSCs) can be limitlessly expanded and differentiated into almost all cell types. Moreover, they are amenable to gene manipulation and, because they are established from somatic cells, can be established from essentially any person. Based on these characteristics, iPSCs have been extensively studied as cell sources for tissue grafts, blood transfusions and cancer immunotherapies, and related clinical trials have started. From an immune-matching perspective, autologous iPSCs are perfectly compatible in principle, but also require a prolonged time for reaching the final products, have high cost, and person-to-person variation hindering their common use. Therefore, certified iPSCs with reduced immunogenicity are expected to become off-the-shelf sources, such as those made from human leukocyte antigen (HLA)-homozygous individuals or genetically modified for HLA depletion. Preclinical tests using immunodeficient mice reconstituted with a human immune system (HIS) serve as an important tool to assess the human alloresponse against iPSC-derived cells. Especially, HIS mice reconstituted with not only human T cells but also human natural killer (NK) cells are considered crucial. NK cells attack so-called “missing self” cells that do not express self HLA class I, which include HLA-homozygous cells that express only one allele type and HLA-depleted cells. However, conventional HIS mice lack enough reconstituted human NK cells for these tests. Several measures have been developed to overcome this issue including the administration of cytokines that enhance NK cell expansion, such as IL-2 and IL-15, the administration of vectors that express those cytokines, and genetic manipulation to express the cytokines or to enhance the reconstitution of human myeloid cells that express IL15R-alpha. Using such HIS mice with enhanced human NK cell reconstitution, alloresponses against HLA-homozygous and HLA-depleted cells have been studied. However, most studies used HLA-downregulated tumor cells as the target cells and tested in vitro after purifying human cells from HIS mice. In this review, we give an overview of the current state of iPSCs in cell therapies, strategies to lessen their immunogenic potential, and then expound on the development of HIS mice with reconstituted NK cells, followed by their utilization in evaluating future universal HLA-engineered iPSC-derived cells.